2002
DOI: 10.1128/jvi.76.20.10264-10269.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mimovirus: a Novel Form of Vaccine That Induces Hepatitis B Virus-Specific Cytotoxic T-Lymphocyte Responses In Vivo

Abstract: CD8؉ cytotoxic T lymphocytes (CTLs) are now recognized as important mediators of immunity against intracellular pathogens, including human immunodeficiency virus and tumors. How to efficiently evoke antigen-specific CTL responses in vivo has become a crucial problem in the development of modern vaccines. Here, we developed a completely novel CTL vaccine-mimovirus, which is a kind of virus-size particulate antigen delivery system. It was formed by the self-assembly of a cationic peptide containing 18 lysines an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…However, epitope-based peptides alone cannot elicit competent immune responses (Naz et al 2005). Research has reported that mimovirus vaccines with sizes similar to viruses can induce cellular immunity (Wu et al 2002, Yang et al 2008. Other studies also have indicated that mimovirus vaccines induce cellular and humoral immune responses (Zhang et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, epitope-based peptides alone cannot elicit competent immune responses (Naz et al 2005). Research has reported that mimovirus vaccines with sizes similar to viruses can induce cellular immunity (Wu et al 2002, Yang et al 2008. Other studies also have indicated that mimovirus vaccines induce cellular and humoral immune responses (Zhang et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Construction of mimovirus took place as described previously (Wu et al 2002). Briefly, the mimovirus was prepared in microcentrifuge tubes by adding plasmids P1 and P2 to TAT [49][50][51][52][53][54][55][56][57] with different molar ratios (0, 0.5, 1, 2, 4, 8, and 16) in HEPES-buffered saline containing 10 mM HEPES and 150 mM NaCl.…”
Section: Construction and Identification Of Mimovirusmentioning
confidence: 99%
See 2 more Smart Citations
“…Wu et al [43] also developed an innovative minovirus vaccine to induce hepatitis B virus specific cytotoxic T-lymphocyte responses. They proved that their mimovirus could induce an HBsAg28-39-specific CTL response in vivo.…”
Section: Therapeutic Vaccinationmentioning
confidence: 99%